The Effect of Agility Training on Soccer Dribbling Skills Among Persije FC Players in South Bengkulu Regency - Akhmad Banda Niji; Feby Elra Perdima; Ajis Sumantri (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of agility training on soccer dribbling skills among Persije FC players in South Bengkulu Regency. Using a total sampling method, the study included 15 Persije FC players from South Bengkulu Regency. This experimental study employed a one-group pretest-posttest design, a pre-experimental design that involves a pretest (test administered before treatment) and a posttest (test administered after treatment) within a single group. Data were collected using test scores. Descriptive data analysis and the t-test were used. The results of this study indicate that agility training has an effect on the ball-dribbling skills of Persije FC players in South Bengkulu Regency, with a calculated t-value of 2.959 and a critical t-value of 1.761, at a significance level of α = 0.05 and df = 14.